Learning by effective utilization of technologies : facilitating intercultural understanding. - Mizoguchi, Riichiro, ....-; Dillenbourg, Pierre, ....-; Zhu, Zhiting, ....- (Amsterdam : IOS, 2006)
A major theme of this book is the use of computers for supporting collaborative learning. This is not surprising since computer-supported collaborative learning has become both a widespread educational practice and a main domain of research. Moreover, collaborative learning has deep roots in Asian educational traditions. Given the large number of researchers within this field, its scope has become very broad. Under this umbrella, one finds a variety of more specific topics such as: interaction analysis, collaboration scripts (e.g. the Jigsaw script), communities of practice, sociocognitive conflict resolution, cognitive apprenticeship, various tools for argumentation, online discussion or collaborative drawing tools (whiteboards), collaborative writing and the role of facilitators. Most research work on collaborative learning focuses on interactions rather than on the contents of environments, which had been the focus in the previous decades of learning technology research. However, there is no reason to focus on one aspect to the detriment of the other. The editors are pleased that the selected papers also cover multiple issues related to the storage, representation and retrieval of knowledge: ontologies for learning environments and the semantic web, knowledge bases and data mining, meta-data and content management systems, and so forth. This publication also reveals a growing interest for non-verbal educational material, namely pictures and video materials, which are already central to new popular web-based applications. This book includes contributions that bridge both research tracks, the one focusing on interactions and the other on contents: the pedagogical use of digital portfolios, both for promoting individual reflections and for scaffolding group interactions.
Keywords: Computers -- Onderwijs; Coöperatief leren